The Employment Challenge in the Maghreb - Benhassine, Najy (World Bank, Washington, DC, 2012)
Generating more and better quality jobs with higher productivity probably constitutes the most important challenge the Maghreb countries will face over the next decade. Despite relatively high and sustained economic growth since 2004, employment creation has been insufficient to significantly reduce unemployment, or to absorb the flow of youth joining the labor market. As a result, the unemployment rate remains high among youth, and has been rapidly increasing among secondary education students and university graduates. In addition, most new jobs are of low productivity, often in the informal sector and benefiting the less educated.